The COVID-19 pandemic impact on the Polish medical personnel work: a survey and in-depth interviews study - Przyłęcki, Paweł; Wieczorkowska, Magdalena; Pawlak-Kałuzińska, Agnieszka; Cedrowska-Adamus, Wioletta; Gulczyńska, Ewa (Frontiers in Public Health, 2023)
The novel SARS-CoV-2 virus required new organizational protocols in medical facilities and changed routine activities of health care workers (HCWs). Physicians, nurses, paramedics, residents, and HCWs were at the forefront combating the unknown disease. The purpose of this paper is to examine how the pandemic affected the tasks and professional activities of HCWs and how it affected relationships with colleagues and patients. We also wanted to know how respondents perceived the engagement of their colleagues and what impact the reality COVID-19 had on the level of perceived stress. We used a mixed-methods approach, distributing an online survey among 215 HCWs and conducting eight semi-structured in-depth interviews. Results show that the organization of medical care was initially chaotic, particularly in the context of hospital care for patients infected with SARS-CoV-2. Organizational changes brought new tasks and shifts that led to uncertainty, increased stress and conflict. The study also identifies the main causes of anxiety that negatively affect the mental health of frontline workers.